Stakeholder Power, Conflict Dynamics, and Sustainable Urban Spring Governance in the Framework of the Sustainable Development Goals - Nurkholis; Mohammad Khusaini; Maharani Pertiwi Koentjoro (Postgraduate, University of Mataram, 2026)
Urbanization pressures and land conversion in Probolinggo City in recent years have increased the risk of discharge reduction and degradation of recharge zones at three main springs: Senthong, Grinting/Sumber Wetan, and Umbul/Ganesha. This study aims to analyze the distribution of power, interests, and conflicts in urban spring conservation. The approach used is a qualitative case study through in-depth interviews, focus group discussions (FGDs), and policy document analysis. The analysis is grounded in Stakeholder Theory using a power–interest matrix instrument to map actor configurations and their relational dynamics. The findings indicate that local government and the water distribution operator (PDAM) occupy dominant positions (high power), while business actors fall into the category of powerful beneficiaries. In contrast, local communities have high interests but low power. This pattern produces pseudo-collaboration practices, in which communities are only involved at the socialization or ceremonial stage, with no role in determining tariff policies, distribution allocation, or conservation priorities. This imbalance triggers latent conflict between exploitation-oriented interests and ecosystem protection agendas. The study concludes that spring conservation requires a governance design that corrects power asymmetry through the establishment of formally legalized cross-actor collaborative forums and the granting of community-based management rights over recharge areas as a mechanism for strengthening substantive participation.